Schaums outline of theory and problems of combinatorics - V K Balakrishnan (New York McGraw Hill Education India Pvt Ltd, 2020)
Combinatorics deals with the enumeration, existence, analysis, and optimization of discrete structures. With this study guide, students can master this growing field-withh applications in several physical and social sciences, including Chemistry, computer Science, operations research, and statistics. Includes hundreds of problems with detailed solutions.
Keywords: Combinational Analyis; Outlines Syllabi; Recurrence Relations; Combinatorics